Rank versus Inequality – Does Gender Composition Matter? - Duk Gyoo Kim; Max Riegel (Center for Economic Studies and ifo Institute (CESifo), 2022)
This study investigates the influence of gender composition on allocation decisions involving a rank–inequality tradeoff. In a laboratory experiment, participants chose to either alleviate inequality by relinquishing their current relative rank or exacerbate inequality by maintaining their current rank. Two essential features of the experiment are: 1) participants' relative rank is the outcome of their real-effort performance and luck; 2) participants' genders are naturally revealed by gender-specific nicknames. We found that female participants are more reluctant to relinquish their current relative rank when the persons ranked below and above them are of the opposite gender. This tendency was less pronounced in the male participants.
Keywords: C91; D63; 330; gender composition; positional concerns; preferences for redistribution; last-place aversion; perception of luck